PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) - sugiyem (Jurnal Riset Daerah, 2022)
This Classroom Action Research aims to improve students' motivation and learning outcomes in learning mathematics through the application of the Two Stay Two Stray (TSTS) type of cooperative learning model. This research was conducted in two cycles with the subjects of class XI MIPA 4 SMA Negeri 1 Bantul. Each cycle is carried out in three meetings with four stages, namely planning, implementation, observation, and reflection. The research instruments used were learning implementation observation sheets, learning motivation questionnaires, and learning outcomes assessment instruments. The results showed that the type of cooperative learning model Two Stay Two Stray (TSTS) can increase students' motivation and learning outcomes in learning mathematics. The average score of the results of the learning motivation questionnaire increased from a score of 101.7 in the high category at the end of the first cycle and reached a score of 105 in the high category at the end of the second cycle. Student learning test results increased from 74.8 at the end of the first cycle and to 85.9 at the end of the second cycle. At the end of the first cycle, the learning motivation has reached the high category, but the average student learning outcomes have not reached the Minimum Mastery Criteria. At the end of the second cycle, students' learning motivation has reached the high category and the average has reached the Minimum Completeness Criteria.